Enhanced composite plate impact damage detection and characterisation using X-Ray refraction and scattering contrast combined with ultrasonic imaging. (15th January 2020) - Shoukroun, D.; Massimi, L.; Iacoviello, F.; Endrizzi, M.; Bate, D.; Olivo, A.; Fromme, P.
Abstract: Ultrasonic imaging and radiography are widely used in the aerospace industry for non-destructive evaluation of damage in fibre-reinforced composites. Novel phase-based X-ray imaging methods use phase effects occurring in inhomogeneous specimens to extract additional information and achieve improved contrast. Edge Illumination employs a coded aperture system to extract refraction and scattering driven signals in addition to conventional absorption. Comparison with ultrasonic immersion C-scan imaging and with a commercial X-ray CT system for impact damage analysis in a small cross-ply carbon fibre-reinforced plate sample was performed to evaluate the potential of this new technique. The retrieved refraction and scattering signals provide complementary information, revealing previously unavailable insight on the damage extent and scale, not observed in the conventional X-ray absorption and ultrasonic imaging, allowing improved damage characterisation.